Dampak Literasi Keuangan dan Sikap Keuangan Terhadap Perilaku Keuangan (The Impact of Financial Literacy and Financial Attitude on Financial Behavior) - Jamal, Hisnol; Haeruddin, Haeruddin; Ahmad, Ibrahim (STIE Malangkucecwara, 2023)
This study analyzes the impact of financial literacy and financial attitudes on the financial behavior of property developers in Gowa Regency. It involves 30 property developers as a census sample. Data were collected using an online questionnaire and analyzed using multiple linear regression with SPSS 25. The results indicate that financial literacy has a positive and significant influence on financial behavior. However, the impact of financial attitudes on financial behavior was not found to be significant. The managerial implication is that property developers should enhance their understanding of financial concepts to optimize their business decisions. Although financial attitudes were not significant in this study, they should still be considered in decision-making. A holistic approach to financial management can provide greater benefits in property business management.